Annie and Snowball and the Thankful Friends : the Tenth Book of Their Adventures - Rylant, Cynthia; Stevenson, Sucie (New York : Simon Spotlight, 2012)
Annie wants to fill every chair in her house's dining room for Thanksgiving dinner, and asks her friend Henry's help in thinking of people to invite.
Keywords: Annie (Fictitious character : Rylant); Snowball (Fictitious character : Rylant); Thanksgiving Day; Neighborliness; Juvenile literature; Beginning to Read; Thanksgiving cooking; Friendship; Thanksgiving Day; Rabbits; Dogs; Cousins